2021
DOI: 10.1038/s41598-021-99102-5
|View full text |Cite|
|
Sign up to set email alerts
|

Longitudinal urinary biomarkers of immunological activation in covid-19 patients without clinically apparent kidney disease versus acute and chronic failure

Abstract: Kidney function is affected in COVID-19, while kidney itself modulates the immune response. Here, hypothesize if COVID-19 urine biomarkers level can assess immune activation vs. clinical trajectory. Considering the kidney’s critical role in modulating the immune response, we sought to analyze activation markers in patients with pre-existing dysfunction. This was a cross-sectional study of 68 patients. Blood and urine were collected within 48 h of hospital admission (H1), followed by 96 h (H2), seven days (H3),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…Creatinine has previously been reported to be a good marker in both muscle tissue 14 . Although it has not been mentioned in literature previously, we also found that neopterin, a biomarker for immune system activation commonly profiled in blood, serum, and urine 58,59 , has a strong negative correlation with PMI. Taurine, also in accordance with studies on vitreous humour 15 , showed a predictable positive behaviour with PMI.…”
Section: Discussionsupporting
confidence: 40%
“…Creatinine has previously been reported to be a good marker in both muscle tissue 14 . Although it has not been mentioned in literature previously, we also found that neopterin, a biomarker for immune system activation commonly profiled in blood, serum, and urine 58,59 , has a strong negative correlation with PMI. Taurine, also in accordance with studies on vitreous humour 15 , showed a predictable positive behaviour with PMI.…”
Section: Discussionsupporting
confidence: 40%
“…This research is exploratory in generating an idea that the immunological response to COVID-19 can be profiled. We found that some of our research overlapped with others [16,17,43,56,60]. Due to the abundance of caution, we did not conduct extensive correlational analysis, which is common in the works of others.…”
Section: Discussionmentioning
confidence: 90%
“…However, invasive techniques have to be used to obtain the sample. Consequently, increasing stress is placed on analyzing other sources of immunological information, including urine, sweat, stool, saliva, and others [35,43,44]. Urine can reflect the immunological performance in general as well.…”
Section: Introductionmentioning
confidence: 99%
“…Lamb et al (2020) previously demonstrated that COVID-19 patients presented elevated levels of proinflammatory mediators such as IL-6, IL-8, and CXCL-10 in urine [ 41 ]. Moreover, Laudanski et al (2021) demonstrated that high urinary IFN-γ at admission was a good predictor of AKI in COVID-19 patients [ 42 ]. Likewise, a proteomic-based study demonstrated that changes in urinary cytokines are associated with AKI development [ 43 ].…”
Section: Discussionmentioning
confidence: 99%